Social relationships in Ranya: An anthropological study - حمەصالح, عزت فتاح; محمد, داڕێژ وریا (Sulaimani Journal for Humanities, 2019)
Social structure each society includes some system (ecology, economic, kinship-social- and culture) each of them linking with each other and relocating, kinship (social) is one of the most important systems which has been studying in Anthropology since it is important and has strong affected to social life. Rnyia city, is community research, which is one of the traditional and historical city in Kurdistan, also has social, ecology, economic and culture specialty. That’s why is one of the society which kinship system is a strong one and has affected individual social life, even this system has been changed as other system by affecting foreign culture , exchange culture and also economic change. The research introduction presents the important, aim and research methodology, also relative system has been presented in three connecting parts (Marriage, Family and Kinship). Finally it introduces the results, suggestion and recommendation.